Pengaruh Kebiasaan Literasi Siswa terhadap Kemampuan Membaca pada Pembelajaran Bahasa Indonesia Kelas 2 SDN Benda 2 - Zuliani, Rizki; Uyun, Nur (Al-DYAS, 2023)
The educational process in schools learning activities are the most basic activities. This means that the success or failure of achieving educational goals as stipulated in the law of the Republik of Indonesia number 20 0f 2003 concerning the national education system, namely”To develop the potential of students to become human being eho believe in and fear god almighty, have noble character, are healthy, knowledgeable, capable creative, independent, and become citizens of a democratic and responsible state.” Very much depends on how the learning process experienced by students as learners. Like a war in learning, students must also be prepared. Namely knowing what things help the success of learning and what often makes th lesson fail. So that a student must understand good study techniques, know the right time to learn to manage time and be disciplined in learning as well as getting used to reading and visitimgm the library which is a storehouse of all reading materials.By carrying out good habits in learning, a student will get high achievement and finally be successful I learning.